Historical foundations of structural litigation in The United States: segregation, power, and jurisdiction (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article examines the historical foundations of structural litigation in the United States, highlighting the importance of judicial decisions in confronting racial segregation. It analyzes how structures of domination, rooted since the colonial period and perpetuated by normative frameworks such as the Jim Crow system and court rulings detached from social reality, such as Plessy v. Ferguson, demanded a new understanding of judicial intervention. Through a deductive methodology, based on bibliographic review and documentary analysis, the study reveals that constitutional omission and the persistence of inequalities required an institutional rupture. The ruling in Brown v. Board of Education II (1955), by requiring the structural implementation of desegregation, represented a fundamental milestone, evidencing the potential of legal hermeneutics in promoting complex social change. It concludes that the American experience offers valuable lessons for Contemporary Law, reinforcing that judicial decisions reach their full potential when committed to social justice and the effectiveness of fundamental rights.
Keywords: Structural Litigation; Racial Segregation; Civil Rights; Supreme Court; Social Justice